People’s perception of pollution of communities and ecosystems: a qualitative study in Kuala Kedah, Malaysia - Ibrahim, Mashitah; Mustari, Sohela (IIUM Press, 2025)
Pollution is a global challenge that threatens human health and ecosystems. Understanding public perception is vital for developing effective policies and promoting sustainability within communities. This study aims to explore local perceptions of pollution affecting communities and ecosystems in Kuala Kedah, Malaysia. It was conducted using a qualitative approach with purposive sampling, and data were collected through semi-structured in-depth interviews. The research examined the experiences, causes, and impacts of pollution on the social, economic, and environmental aspects of local life. Results indicated that pollution in Kuala Kedah mainly originates from human activities, impacting the community's social and economic well-being. The study highlights the importance of public participation in pollution management and offers recommendations for policymakers, academics, and researchers.